The Effect of Honor and Career Development Opportunities on The Supply of The Teacher Workforce - Kuswanto; Kristober Sitompul; Muhammad Arif Liputo (International Journal of Education and Humanities, 2026)
This study is motivated by the imbalance in the distribution and workload of educators in private schools, reflecting a fundamental problem in the supply of teacher labor. Such disparities potentially affect the quality of educational services and the effectiveness of the learning process. Therefore, this study aims to examine the influence of financial compensation (honorarium) and professional factors (career development opportunities) on teachers' labor supply, particularly in the allocation of teaching hours among private senior high school teachers in Jambi City. This research employs a quantitative approach with an associative explanatory design. Data were collected by distributing Likert-scale questionnaires to 94 respondents selected using proportional random sampling. The data were analyzed using multiple linear regression after satisfying the assumptions of classical test statistics. The results indicate that honorarium partially has a positive and significant effect on teacher labor supply (t = 6.489; p = 0.001). Similarly, career development opportunities demonstrate a strong, positive, and significant effect (t = 5.189; p = 0.001). Simultaneously, these two variables account for 62.4% of the variance in teacher labor supply decisions (R² = 0.624). The implications of this study suggest that while adequate financial compensation serves as a fundamental economic basis, the availability of career development opportunities acts as a crucial motivational driver and retention factor. Therefore, an integrated policy combining fair compensation and clear career pathways is highly recommended to ensure the stability and sustainability of the teaching workforce in private schools